Upper Respiratory System Involvement as the Only Manifestation of Granulomatosis with Polyangiitis in a Child with Marfan Phenotype - Amin, Reza (National Research Institute of Tuberculosis and Lung Disease, 2013)
We report a 9-year old girl with an unusual presentation of granulomatosis with polyangiitis in association with Marfan phenotype. The patient presented with recurrent sinusitis, epistaxis, hearing loss and hyperplastic gingivitis, without any signs or symptoms of major organ involvement.